2013
DOI: 10.5267/j.msl.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of information technology on strategic management: A case study of after sale services

Abstract: Information technology plays essential role on the success of organizations; it eases the access on information, reduces time on reaching the necessary information and builds a better communication among different groups of an organization. This paper performed an empirical investigation to find the effects of information technology on strategic management in one of Iranian automakers in after sales services in Iranian auto industry. The proposed study designed questionnaire and distributed among some experts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The contributions relate to the functional viability of this municipal information as well as information technology management initiative and the specifics of its approach execution. Farnia et al [11] conducted an empirical study to assess the impact of IT on strategic controlling at one of Iranian auto manufacturers on after-sales facilities in the Iranian automotive business. The findings suggested that information technology had an impact on the implementation and management policies of the strategy.…”
Section: Strategic Use Of Information Technologymentioning
confidence: 99%
“…The contributions relate to the functional viability of this municipal information as well as information technology management initiative and the specifics of its approach execution. Farnia et al [11] conducted an empirical study to assess the impact of IT on strategic controlling at one of Iranian auto manufacturers on after-sales facilities in the Iranian automotive business. The findings suggested that information technology had an impact on the implementation and management policies of the strategy.…”
Section: Strategic Use Of Information Technologymentioning
confidence: 99%